Analisis Penentuan Harga Pokok Produksi Padi Sawah Di Desa Kauditan I Kecamatan Kauditan Kabupaten Minahasa Utara - Panggalo, Keren; Pangemanan, Lyndon Reindhart Jacob; Taroreh, Melissa Lady Gisela (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This study aims to calculate the cost of production of paddy rice in Kauditan I Village, Kauditan District, North Minahasa Regency and compare farmers’ income with the Provincial Minimum Wage (UMP). The sampling method in the study was purposive sampling. The research data were collected using primary data obtained from surveys and interviews while secondary data were obtained from relevant agencies related to this research. Data analysis used to calculate the cost of goods produced is the Full Costing method. The results showed that the cost of production calculated with the Full Costing approach on land area ≤ 0.5 amounted to Rp. 6,662 per kg, on land area 0.5 - 1 amounted to Rp. 7,148 per kg and on land area ≥ 1 amounted to Rp. 6,894 per kg. The average cost of rice production in Kauditan I Village is Rp. 6,901 per kg and farmers’ income is still below the Provincial Minimum Wage.